Ultrahromatizm as a Sound Meditation - Zaytseva, Marina (Traektorii͡a︡ nauki : mezhdunarodnyĭ ėlektronnyĭ nauchnyĭ zhurnal, 2016)
The article scientifically substantiates the insights on the theory and the practice of using microchromatic in modern musical art, defines compositional and expressive possibilities of microtonal system in the works of composers of XXI century. It justifies the author's interpretation of the concept of «ultrahromatizm», as a principle of musical thinking, which is connected with the sound space conception as the space-time continuum. The paper identifies the correlation of the notions «microchromatism» and «ultrahromatizm». If microchromosome is understood, first and for most, as the technique of dividing the sound into microparticles, ultrahromatizm is interpreted as the principle of musical and artistic consciousness, as the musical focus of consciousness on the formation of the specific model of sound meditation and understanding of the world. В статье научно обоснованы выводы по теории и практике использования микрохроматики в современном музыкальном искусстве, определены композиционные и выразительные возможности микрохроматики в сочинениях композиторов XXI века. Обосновано авторское понимание «ультрахроматизма» как принципа музыкального мышления, связанного с представлениями о звуковом пространстве как пространственно-временном континууме. В работе выявлено соотношение понятий «микрохроматизм» и «ультрахроматизм». Если под микрохроматизмом понимается, прежде всего, техника деления звука на микрочастицы, то ультрахроматизм трактуется как принцип музыкально-художественного сознания, как направленность музыкального сознания на формирование особой модели звукосозерцания и миропонимания. У статті науково обґрунтовані виводи щодо теорії і практики використання мікрохроматики у сучасному музичному мистецтві, визначені композиційні і виразні можливості мікрохроматики у творах композиторів XXI століття. Обґрунтовано авторське розуміння «ультрахроматизму» як принципу музичного мислення, пов'язаного із уявленнями про звуковий простір як просторово-часовий континуум. У роботі виявлено співвідношення понять «мікрохроматизм» і «ультрахроматизм». Якщо під мікрохроматизмом розуміється, передусім, техніка поділу звуку на мікрочастини, то ультрахроматизм трактується як принцип музично-художньої свідомості, як спрямованість музичної свідомості на формування особливої моделі звукоспоглядання і світобачення.